Analisis Kebutuhan Hierarki Tokoh Dimas Suryo pada Novel Pulang Karya Leila S. Chudori - Mustikawati, Arih; Nur Sholichah, Dwirini; Kurniawan, Eva Dwi (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2023)
The purpose of this study is to see the fulfillment of physiological needs, the need for security, the need for love and existence, the need for appreciation and the need for self-actualization in the characters in the novel Pulang by Leila S. Chudori. The character Dimas Suryo experiences instability in fulfilling hierarchical needs due to external conditions that affect his life. The method used uses a literary psychology approach. Data collection is done by reading, marking, and grouping data. Based on the results obtained, it shows that the unfulfillment of hierarchical needs such as physiological needs, the need for security, the need for love and acceptance, the need for appreciation and recognition and self- actualization amid difficult socio-political conditions in the character Dimas Suryo in the novel Pulang by Leila S. Chudori.